2017
DOI: 10.1016/j.jart.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent strain at large shear deformation: Theoretical, numerical and finite element analysis

Abstract: In this study, effective strain is evaluated for large simple/pure shear deformations and new expressions are derived. The validity of these relations was checked by numerical calculations. In addition, finite element analysis of simple shear and pure shear modes of deformation was conducted using ABAQUS software. Additionally, two other major expressions for evaluating effective strain at large simple shear deformation were investigated and compared with finite element results. Based on FEM results, the linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Hyperelastic constitutive models in ABAQUS have been widely used 11,35,39–41 . If only uniaxial tensile test results are provided, the Marlow hyperelastic model will be recommended, 37,39 whose strain energy function is the result of integrating the provided nominal stress–strain test data 42–44 . Therefore, this model has no explicit mathematical expression and material parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperelastic constitutive models in ABAQUS have been widely used 11,35,39–41 . If only uniaxial tensile test results are provided, the Marlow hyperelastic model will be recommended, 37,39 whose strain energy function is the result of integrating the provided nominal stress–strain test data 42–44 . Therefore, this model has no explicit mathematical expression and material parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the true out‐plane normal stress σz is basically equal to σnomz, and the true out‐plane normal strain εz can be expressed as εzgoodbreak=ln()1goodbreak+εnomzεnomz During out‐plane shear deformation, the true out‐plane shear stress τkz is just the same as τnomitalickz since the overlapping area remains unchanged. However, different from the nominal out‐plane shear strain γnomitalickz, the true out‐plane shear strain 37,38 γkz is γkzgoodbreak=tan1γnomitalickzgoodbreak=tan1()δhnormalsz …”
Section: Systematical Test Procedures and Materials Parametersmentioning
confidence: 99%
“…Due to this mechanism, tensile residual stress ultimately remains in the weld. The equivalent strain method based on inherent strain has been proposed to implement such a mechanism and has been used by various researchers to study welding characteristics [20,21].…”
Section: Inherent Strain Methodsmentioning
confidence: 99%
“…Pardis et al [46] demonstrated using simple geometric relationships that the shear strain can then be calculated as…”
Section: Finite Element Frameworkmentioning
confidence: 99%